If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2p + -7) + 6 = 11 Reorder the terms: (-7 + 2p) + 6 = 11 Remove parenthesis around (-7 + 2p) -7 + 2p + 6 = 11 Reorder the terms: -7 + 6 + 2p = 11 Combine like terms: -7 + 6 = -1 -1 + 2p = 11 Solving -1 + 2p = 11 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2p = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 2p = 11 + 1 2p = 11 + 1 Combine like terms: 11 + 1 = 12 2p = 12 Divide each side by '2'. p = 6 Simplifying p = 6
| 19x=226 | | 6y^2-10y=2y | | 10k-[4k+(-4+4k)]= | | (7+7i)-(-6-i)= | | 7x-11=-109 | | 59=-4s+8 | | 6+3(5x-6)=6-4(2x+1) | | 3b^0.5(2b^0.5+5b^3/2) | | -14+6x+7=2x+1+5x | | by=a+x | | yb=x+a | | -2(7x-1)+7=-14x+9 | | (4+9i)+(5-8i)= | | 3(4x-2)=-2(-6x+3) | | 10m^2=2m+3.14159 | | 8=-7x+4+2 | | 2(15d+45c)+5/6(12d+18c) | | 5*-1+4*5= | | 16=4x-5 | | -2k^2+72=0 | | y-12=0.666(x-6) | | -4x-1/2y=10 | | -7=4r | | 3c-2d=2 | | 3/4x-5-7/3x-1 | | 3b^1/2(2b^1/2+5b^3/2) | | 5(2x+8x)=0 | | 3x+5=12x-20 | | 3=2c-11 | | -d+-18=0 | | 1566-853= | | x*13+15=x*5+207 |